OPTIMIZATION OF THE TECHNOLOGICAL PROCESS OF THE FERROCHROME PRODUCTION OUT OF WASTE OF TANNING PRODUCTION - O. S. Komarov; I. B. Provorova; V. I. Volosatikov; D. O. Komarov; V. V. Melnichenko (Литьë и металлургия)
The article touches upon the solving of the actual problem — production in conditions of Belarus of ferrochrome of the leather production wastes, that allows to solve several technological problems and to reduse import of expensive ferroallows.